Body language I [ beyond words - Gallagher, Anne (Learning Seed, 2008)
This program is an informative look into the fascinating world of nonverbal communication. It guides viewers through the land of space wars, tongue showing, mirrored postures, and the many layers that make up unspoken communication. -- website